Proteomics of sea bass skin-scales exposed to the emerging pollutant fluoxetine compared to estradiol - Pinto, Patricia (2022)
Teleost fish skin-scales are essential for protection and homeostasis and the largest tissue in direct contact with the environment, but their potential as early indicators of pollutant exposure are hampered by limited knowledge about this model. This study evaluated multi-level impacts of in vivo exposure of European sea bass to fluoxetine (FLX, a selective serotonin-reuptake inhibitor and an emerging pollutant) and 17 beta-estradiol (E2, a natural hormone and representative of diverse estrogenic endocrine-disrupting pollutants). Exposed fish had significantly increased circulating levels of FLX and its active metabolite nor-FLX that, in contrast to E2, did not have estrogenic effects on most fish plasma and scale indicators. Quantitative proteomics using SWATH-MS identified 985 proteins in the scale total proteome. 213 proteins were significantly modified 5 days after exposure to E2 or FLX and 31 were common to both treatments and responded in the same way. Common biological processes significantly affected by both treatments were protein turnover and cytoskeleton reorganization. E2 specifically up-regulated proteins related to protein production and degradation and down-regulated the cytoskeleton/extracellular matrix and innate immune proteins. FLX caused both up- and down-regulation of protein synthesis and energy metabolism. Multiple estrogen and serotonin receptor and transporter transcripts were altered in sea bass scales after E2 and/or FLX exposure, revealing complex disruptive effects in estrogen/serotonin responsiveness, which may account for the partially overlapping effects of E2 and FLX on the proteome. A large number (103) of FLX-specifically regulated proteins indicated numerous actions independent of estrogen signalling. This study provides the first quantitative proteome of the fish skin-scale barrier, elucidates routes of action and biochemical and molecular signatures of E2 or FLX-exposure and identifies potential physiological consequences and candidate biomarkers of pollutant exposure, for monitoring and risk assessment.